PROGRAM PENGEMBANGAN PARIWISATA AIR TERJUN GURUH GEMURAI DI KABUPATEN KUANTAN SINGINGI - Hurriyati, Yaumil; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Program development tourism waterfall Guruh Gemurai in Kuantan Singingi distrik. The purpose of this study was to determine how the program of tourism development waterfall Guruh gemurai in Kuantan Singingi district. In this study the authors use descriptive study kualitataif with research sites in the Department of Tourism Culture Youth and Sport Regency Kuantan Singingi The survey results revealed that the implementation of the Department of Tourism, Youth and Sports Kebudayan Regency Kuantan Singingi in tourism development waterfalls thunder Gemurai tourism destinations such as program development, tourism marketing programs, and partnership development program. In the implementation of the above program have not been realized to the fullest. This was caused by several factors inhibiting the limited funding, the lack of human resources, infrastructure.Kata kunci: Program, pengembangan pariwisata, factor-faktor penghambat.